Mechanizmy dystrybucji dochodu rozporządzalnego w gospodarstwach domowych - w poszukiwaniu paradygmatu - Rószkiewicz, Małgorzata (Mechanisms of Disposal of Income Distribution in Households, 2006)
According to Keynes (1936), consumption is dependent on two groups of determinants, the first being of an objective character - including economic determinants which influence the individual's income, while the second one is of a subjective character and refers to the needs, customs and psychological predisposition, as well as generally established rules and habits regarding income distribution. The primary conclusion following from Keynes's theory was the classification of subjective factors as stable in a short period of time and hence making consumption and savings accumulation dependent only on those factors which affect an individual's income level. Both parts of such an economic approach were challenged and criticized by Katona (1975), whose studies started a new field in economics, known as psychological economics. According to the author, maximizing utility is not the basic criterion of human activity and in a similar vein, of economic behaviour. A rationalistic vision of human beings was contrasted with statements of psychological character. The problem of restraint in spending as a consequence of the income pressure was mentioned only sporadically and treated more as an anomaly. The restraint as a basic factor affecting consumption is considered in the concepts of behavioural life-cycle hypothesis by Shefrin and Thaler (1988) which key assumption is that households treat components of their wealth as absolutely nonfungible. In this theory wealth is assumed to be divided into three mental accounts: current income, current assets, and future income, and spending from current income is more tempting than spending form future income.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 87-97